Problem of Educational Facilities and Infrastructure in MTs Muhammadiyah 15 Medan - Sri Wahyuni Silalahi; Nurzannah Nurzannah (Universitas Muhammadiyah Enrekang, 2024)
This research was conducted to find out what problems there are in the management, use, procurement and maintenance of infrastructure and what steps and solutions are being taken at Mts Muhammadiayah 15 Medan. Researchers use qualitative methods with the Field Research Model. In conducting data analysis, the author used a descriptive approach with the Miles and Huberman model with data collection techniques in the form of observation, interviews and documentation of students and teachers as data sources / primary informants. Meanwhile, in data analysis, the author carried out data collection, data reduction, and presented the data in the form of a short description. With this research, the author hopes to find out the quality of management, use, procurement and maintenance of educational facilities and infrastructure at Mts Muhammadiyah 15 Medan.